Pengaruh Pendidikan Kesehatan dengan Media Audiovisual Manajemen Laktasi terhadap Tingkat Pengetahuan dan Self Efficacy Ibu Menyusui - Citrawati, Ni Ketut; Hapsari, Elsi Dwi; Widyandana, Widyandana (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Infant mortality rate in Indonesia in 2012 is 32 per 1,000 live births. It is less pleasant ifcompared to the target Ministry of Health of Republic of Indonesia tries to achieve, which is 24 by 2014. The low rate of breastfeedingto one of the dominant factor that cause the mortality it is influenced by several factors, in which one of them is the mother’sknowledge about breast milk and breastfeeding. Health education on lactation management may help increase mothers’ ability to gain information as well as their confidence to breastfeeding their baby.Objective: This research is conducted with the purpose to know the effect of health education with audiovisual on lactation management to the level of knowledge and self-efficacy among breastfeeding mothers.Method: This research is categorized as quasi experimental one, whose design applies pre-test and post-test non-equivalent control group. It is conducted toward 32 breastfeeding mothers who receive health education as the treatment group, and to 32 breastfeeding mothers who are asked to read modules about breastfeeding as the control group. The sampling technique applies purposive sampling and simple random sampling. Data are processed by computer programs using Mann-Whitney test, Wilcoxon test, and linear regression model.Result and Discussion : The score for the value of knowledge before treatment among both groups were relatively similar (p>0.05). After treatment, both groups have improvement, (p<0.05). The score of self-efficacy before treatment among both groups did not have significantly different (p>0.05). compared to control group, the intervention group has significantly higher score of knowledge (p>0.05)Conclusion: Health education by audiovisual media and modules are more effective to improve the knowledge and self-efficacy among breastfeeding mothers compared to by only modules.Keywords: Health education, Audiovisual, Modules, Knowledge, Breastfeeding, Self-Efficacy